Improving Students' Reading Through The Use of Illustration Pictures at Class VIII B SMPN 2 Kragan - Arif Rohman Hakim; Arif Rohman Hakim (Universitas Nahdlatul Ulama Sunan Giri Bojonegoro, 2024)
This research aims to know whether illustration pictures may improves the reading of Class VIII B of SMPN 2 Kragan who found it difficult to adapt to regular classroom environment from years of e-learning. The theory of the research is based on the DCT Theory by Clark and Paivio. The researcher used Classroom Action Research, the researcher acts as collaborator, while the teacher acts as the implementator. The technique used in this research is illustration pictures. This research consists of two cycles, and each consists of four meetings. There are 32 students as participants. Three research instruments utilized in this research are test, observation, and interview. The findings of the research demonstrates that using illustration pictures to improve the students’ reading comprehension resulted in success. The students’ average score in pre-test is 50,625, the students’ average score in post-test 2 is 79,125, which means growth from the pre-test to post-test 2 is 56,29%. This research also resulted in students become more attentive to the learning and the classroom condition is more suitable to let the students adapt from e-learning to regular classroom environment. A conclusion can be made that illustration pictures technique is successful to improve students’ reading comprehension. Keywords: illustration pictures, reading, classroom action research